Pengembangan Media Mobile Learning Pelajar Nusantara untuk Pembelajaran PPKn SMA/SMK/MA Kelas X - Anggraini, Elika Yulita; Santoso, Minto; Rarasati, Ida Putri (Universitas Muhammadiyah Ponorogo, 2023)
Based on initial observations at SMA/SMK/MA, problems were found in Civics learning, namely the use of instructional media that was not yet effective. So far, online learning has only used whatsapp groups. By finding these problems, effective and innovative learning media are needed, one of which is mobile learning media. This study aims to determine the development of mobile learning media for Indonesian students and to find out the test results for the use and readability of teachers and students towards the media. This study uses a qualitative descriptive approach. Data collection techniques used questionnaires, observation sheets, and interview sheets. This development produces a product in the form of Indonesian Student Mobile learning media with the results of validation by material experts in the percentage of 89% in the very valid category, media experts in the percentage of 85.5% in the very valid category, and linguists in the percentage of 84% in the very valid category. The results of the test on the use of media on student percentages are 89% with very high criteria, and the results of the teacher use test are 95% with very high criteria. The results of the readability test for students were 82.3% with very high criteria, and the results of the readability test for teachers were 92.5% with very high criteria. With this validation assessment it shows that the use of Mobile Learning media is valid, good, feasible and gets a positive response from students and teachers, so that the media can be used in Class X PPKn learning at SMA/SMK/MA level schools.